DEVELOPING A HEALTHCARE TECHNOLOGY: HOW WE ENGAGED RATHER THAN EXCLUDED OLDER ADULTS. (11th November 2018) - Huisingh-Scheetz, M; Hawkley, L; Nicholson, R
Abstract: Regular exercise and social engagement are essential to maintaining physical and cognitive independence and quality of life among older adults. However, frail and homebound older adults face incredible challenges to maintaining exercise and social engagement. Furthermore, the healthcare system does not currently offer long-term support for these activities. New technology has the potential to help connect frail older adults and their caregivers to rehabilitation and socialization in the home, but its development requires a unique approach for this audience. We will discuss how we have developed a technology-based solution targeting older adults and their caregivers to support long-term exercise and social engagement. We will share our iterative participatory design methodology that incorporated older adult and caregiver input during the design process, which helped make the product both relevant and user-friendly to targeted users.